Theoretical study of the double concave friction pendulum system under variable vertical loading. Issue 8 (June 2019) - Zhou, Fangyuan; Xiang, Weilin; Ye, Kun; Zhu, Hongping
The double concave friction pendulum system has been recognized as an efficient device for decreasing the seismic response of a structure during an earthquake excitation. Previous studies have focused mainly on the properties of the double concave friction pendulum system under constant vertical loading, and the width of the hysteretic loop changed by the vertical ground motion is less considered. In view of this, a theoretical study of the double concave friction pendulum system under variable vertical loading is conducted in this article. Meanwhile, the properties of the hysteretic loops of the double concave friction pendulum system with different friction coefficients between the articulated slider with the upper and lower sliding surfaces are investigated. The results show that the hysteretic loops of the double concave friction pendulum system will be affected by the variation of the vertical loading and the difference of the friction coefficients between the articulated slider with the upper and lower sliding surfaces.